The potential effects of federal health insurance reforms on employment arrangements and compensation - Marcus Dillender; Carolyn J. Heinrich; Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 2015)
The Affordable Care Act (ACA) presents an opportunity to significantly improve compensation for American workers. A potential concern, though, is that employers will circumvent the employer mandate by increasing their use of workers in staffing arrangements that are not covered by the mandate: workers averaging less than 30 hours per week, working on a temporary basis, or working in organizations with fewer than 50 full-time employees. In this paper, we shed light on the likely effects that the ACA will have on employment arrangements. We first examine how part-time employment in Massachusetts changed after its health insurance reform, which is similar to the ACA in many ways. We find, contrary to prior research, that the Massachusetts reform resulted in modest increases in part-time employment among low-educated workers. We then identify the characteristics of employers and employees most affected by the ACA's employer mandate. For the period 2010 to 2012, we estimate that workers who were not offered health insurance at their workplaces but whose employers would be required to offer health insurance under the ACA made up about 5 percent of the workforce and that reducing average weekly hours worked may be relatively straightforward for employers in industries with the largest concentrations of these workers (e.g., retail trade and accommodation and food services). We also point to recent industry patterns of involuntary part-time employment and temporary help use that are consistent with these potential effects of the employer mandate.
Keywords: I13; J3; 330; Affordable Care Act; temporary help; part-time